Implementation of High-Resolution Non-penetrating Cortical Thin-Film Electrodes in the Awake Craniotomy for Research. (16th November 2020) - Stedelin, Brittany; Cleary, Daniel; Paulk, Angelique; Bourhis, Andrew; Dayeh, Shadi; Tchoe, Youngbin; Halgren, Eric; Raslan, Ahmed M.T
Abstract: INTRODUCTION: Cortical mapping in an awake patient prior to the resection of pathologic neuronal tissue affords the unique opportunity to record task-based electrophysiological data directly from the pial surface. The development of high density thin-film microelectrodes has greatly enhanced the resolution of electrocorticographic recordings obtained intraoperatively. METHODS: 128 and 1024-channel poly(3, 4‐ethylenedioxy-thiophene):poly(styrenesulfonate) electrodes were manufactured and used for intraoperative research recordings at a single center and shipped for use at two additional centers. Obstacles encountered in the in the pre-hospital, on-site, intraoperative and extraoperative settings, and how they were addressed is described. 25 subjects performed intraoperative behavioral tasks with a high-density cortical microgrid in place. Factors affecting the quality of the recordings obtained, number of working channels, and ease of implementation were noted and summarized here. 1024-channel microgrid Motor and sensory task in process RESULTS: The number of functional channels was consistently reduced during the steam-based gravity autoclave cycle. The addition of a solid extender board to the end of the electrode greatly reduced the rate of electrode destruction by increasing the ease at which the sterile electrode preparation and subsequent interface with the non-sterile acquisition board was executed. Stabilization of the acquisition board using a Greenberg retractor system reduced the amount of movement artifact. Impedence measurement Sterile electrode and non-sterile acquisition board interface Acquisition board stabilized with Greenberg retractor system CONCLUSION: High-resolution eCog recordings with yields up to 771 working channels with relatively low noise can be reliably obtained during awake craniotomy procedures. Effective communication between teams producing, preparing, and using high-density cortical microgrids for research is imperative. Proper handling during sterile processing, cautious sterile preparation in the operating room, and meticulous planning regarding operating room configuration help ensure success in obtaining useful recordings. Incorporation of task-based high-density microelectrode recordings during awake craniotomy procedures represents an avenue for discovery into the anatomy and physiology of eloquent regions of the human brain on both a microscopic and macroscopic level.